Study on Microscopic Pore Structure Characteristics of Tight Sandstone Reservoir - Zhou, Xing (International Journal of Electric Power and Energy Studies, 2024)
The micro-nano scale pore throat of tight sandstone reservoir (TSR) will have a significant impact on the macroscopic seepage capacity of the reservoir. Based on X-ray diffraction (XRD), cast thin section (CTS), scanning electron microscopy (SEM), CT scanning and other testing methods, this paper studies the microscopic pore structure characteristics of tight sandstone reservoirs. The experimental results show that the quartz content of the core samples of the Chang 8 section of the tight sandstone reservoir is the highest, with an average value of 44.19%. The second is plagioclase, with an average content of 21.71%. The core samples are mainly fine-grained quartz sandstone and feldspar lithic sandstone, which are light gray as a whole, with poor oil content and basically no crude oil. The throat types are mainly flake and curved flake throats, and some tube bundle throats are developed. The maximum length of the flake throat is 348.80μm, and the width of the tube bundle throat stenosis is only 13.40μm. The total pore volume of low permeability core is 1.25×107μm3, and the volume percentage is 1.19%. The volume of connected pores is 3.49×106μm3, the volume percentage is 0.33%, and the proportion of connected pores is very low.